Family Function and Quality of Life in Elderly in Palu City, Indonesia (Indian Journal of Public Health Research & Development, 2020)
To analyze the function of the family towards the quality of life in elderly in Palu City, which is expectedto be a basis for the target of a health promotion program on the quality of life in elderly. The researchmethod used an analytic survey of the elderly in the city of Palu. The sample size was 390 respondents. Thesample was the 189 elderly victims of natural disaster who lived in the Temporary Shelter (Huntara) andthe 201 elderly people who did not live in the Non-Temporary Shelter (Non-Huntara) which conducted inMay - June 2019. The research variable was measured by using questionnaires. The characteristics of elderlynamely: Age, gender, education, working status, ethnicity, marital status, history of illness, and history offalls. Family function (A = Adaption, P = Partnership, G = Growth, A = Affection, R = Resolve). The qualityof life in eldery was measured by using the questionnaires of WHOQOL-BREF. The data analysis usedunivariate and bivariate analysis with the SPSS application. The results of the study showed that respondentswere 53.33% women and 46.67% men, with 47.95% were junior high school graduated and 73.85% werenot working. 67.18% elderly were married. Elderly who has a history of illness of 57.69% and history of fallof 36.92%. Mean score of adaption = 1.49, partnership = 1.44, growth = 1.47, affection = 1.29, and resolve= 1.37. Total mean score of APGAR was 7.07. The mean score of physical dimension = 21.7, psychologicaldimension= 19.9, social relationship dimension = 9, dan environmental dimension = 23.4. The total meanscore of quality of life was 74.0. It can be concluded that the family had a good function (score 7.07) for theelderly and the quality of life in elderly was good (score 74.0).
Keywords: : family function, quality of life, elderly.